2020
DOI: 10.1021/acs.biomac.0c00347
|View full text |Cite
|
Sign up to set email alerts
|

Injectable and Self-Healing Nanocomposite Hydrogels with Ultrasensitive pH-Responsiveness and Tunable Mechanical Properties: Implications for Controlled Drug Delivery

Abstract: Injectable, self-healing, and pH-responsive hydrogels are great intelligent drug delivery systems for controlled and localized therapeutic release. Hydrogels that show pH-sensitive behaviors in the mildly acidic range are ideal to be used for the treatment of regions showing local acidosis like tumors, wounds and infections. In this work, we present a facile preparation of an injectable, self-healing, and supersensitive pH-responsive nanocomposite hydrogel based on Schiff base reactions between aldehyde-functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 75 publications
0
107
0
Order By: Relevance
“…For instance, pH‐responsive nanocomposite hydrogels designed to activate in acidic conditions will exhibit greater network degradation at profoundly acidic pH (≈3.0) compared to mildly acidic pH (≈6.5) environments. [ 31 ] As a result, stimuli‐responsive platforms will remain dormant, that is, inactive but receptive to incoming inputs if: i) the stimuli intensity/parameters do not meet the required recognition threshold, or ii) if they are of a different nature/type that the system is not designed to recognize (i.e., pH‐responsive platform unable to identify incoming light inputs). Overall, this communication code resembles that present at the tissue level, where pathways recognize specific types of biomolecular inputs (i.e., ligands, substrates, growth factors, etc.)…”
Section: Design Blueprints For Stimuli‐responsive Nanocomposite Hydromentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, pH‐responsive nanocomposite hydrogels designed to activate in acidic conditions will exhibit greater network degradation at profoundly acidic pH (≈3.0) compared to mildly acidic pH (≈6.5) environments. [ 31 ] As a result, stimuli‐responsive platforms will remain dormant, that is, inactive but receptive to incoming inputs if: i) the stimuli intensity/parameters do not meet the required recognition threshold, or ii) if they are of a different nature/type that the system is not designed to recognize (i.e., pH‐responsive platform unable to identify incoming light inputs). Overall, this communication code resembles that present at the tissue level, where pathways recognize specific types of biomolecular inputs (i.e., ligands, substrates, growth factors, etc.)…”
Section: Design Blueprints For Stimuli‐responsive Nanocomposite Hydromentioning
confidence: 99%
“…Recently, researchers developed injectable, self‐healing and super‐sensitive pH‐responsive nanocomposite hydrogels through dynamic covalent Schiff base linkages between amine‐functionalized silica nanoparticles and pendant aldehyde moieties in zwitterionic polymers ( Figure A). [ 31 ] Such cytocompatible nanocomposite hydrogels could be rapidly assembled (< 10 s) in physiological conditions (pH ≈ 7.4) by simply homogenizing a solution containing both polymer and silica nanoparticles. As expected, increasing either hydrogel polymer or nanoparticle content led to substantially enhanced elastic moduli by increasing the density of Schiff base linkages.…”
Section: Stimuli‐responsive Nanocomposite Hydrogels and Biomedical Apmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, upon studying the pH-responsive model drug release behavior in vitro, the authors found that the release rate of the model organic molecules gradually increased with an increase in the medium acidity, due to the NC hydrogel's acidic pH-dependent degradation and swelling behavior. [121] Boronic acid-based building blocks are also very useful for the generation of dynamic bond crosslinked pH-responsive hydrogels. For example, 2-formylphenylboronic acid (2-FPBA), through its aldehyde group, can form dynamic imine bonds with primary amines.…”
Section: Ph-responsive Injectable Hydrogels For Controlled and Local mentioning
confidence: 99%
“…A number of these studies use small benzaldehyde crosslinkers, such as bi-, tri-, or tetra-functional PEGs, however, fewer reports exist on the use of high molecular weight crosslinkers with higher degrees of functionality. [37][38][39] In one example, Cao et al 39 , used anionic polymerization to synthesize a multi-benzaldehyde functionalized PEG analogue crosslinker to form injectable hydrogels after in situ reaction with glycol chitosan. Hydrogels showed controlled gelation times and long term degradation profiles important for the encapsulation of chondrocytes for cartilage tissue applications.…”
Section: Introductionmentioning
confidence: 99%